Efficacy of Wikipedia as a pedagogical apparatus in the classroom - Malissa Maria Mahmud, *; Wong, Shiet Ching * (SAVAP International, 2013)
The profusion of the information and communication technology has allowed institution of higher education educators and users to experiment variety of apparatus accessible that can be employed as instructive devices in the classrooms. Wikipedia personifies a fascinating and novel concept which can be used to engage students in authentic collaborative writing activities. This paper provides a description of how Wikipedia was incorporated as a pedagogical means in the ESL settings and reports on the students’ attitude and perception on the use of Wikipedia to enhance their L2 proficiency specifically their writing skills. The experience involved the use of wiki technology and the advanced collaborative forms and participative assessment as part of the teaching method. Data was gathered through a survey questionnaire concerning a particular group of transfer students at the tertiary stage. By the means of intended framework and structure, the students carried out several stages of the activities established distinctively for the English subject that they enrolled during the spring semester. The questionnaire was then administered and analysis of data in the signified affirmative responses from the students concerning the use of Wikipedia in the learning activities. The results indicate they perceived that the use of Wikipedia had generally enhanced their L2 skills such as reading and writing, expanded their social circles, improved their communication skills and minimized their apprehension when learning and using the language among their peers. The paper concludes by stressing the advantages that can be attained as a result of the implementation of Wikipedia in language learning contexts and success in attempts to provide such support may depend on: knowledge with wiki technology, vigilant preparation for execution and use, apt class size, and motivation of students to engage in unearthing learning.